HUBUNGAN POLA KONSUMSI PROTEIN DENGAN KADAR ASAM URAT DAN KOLESTEROL PADA LANSIA DI DESA JEPUN KABUPATEN TULUNGAGUNG - Yuli Saputri, Berlian; Farida; Masruroh, Eny; Herminaju, Ketjuk; Anggraini, Ria (Jurnal Surya, 2025)
Introduction: Uric acid is the end product of purine metabolism that deposits in tissues and can cause an increase in blood uric acid levels above normal. Increased uric acid levels can lead to disorders in the body if left unchecked. Several factors that influence the occurrence of uric acid include lifestyle factors such as physical activity, consumption patterns, and resting habits This study aimed to determine the Relationship Between Protein Consumption Patterns with Uric Acid and Cholesterol Levels. Methods: This study used is a correlational analytic design. The population in this study consists of 70 people, and the sample used is 60 elderly individuals aged 60-74 years who meet the inclusion and exclusion criteria. Data analysis in this study used the chi-square statistical test. Results: There is a relationship between protein consumption patterns uric acid levels and cholesterol levels in the elderly. (p<0.000). Conclusion: High protein consumption patterns in the elderly are caused by the lack of variety of foods consumed. In addition, the elderly do not know the benefits or effects of the food consumed, they only know that eating a lot will make them healthy.